Ethical Frameworks in Philosophical Traditions - Omonije, Ajibola (Journal of Social Science and Humanities, 2025)
Before we go into the details of ethics in Indian Philosophical thought, we must first of all know what ethics is. Ethics is the study of what is right and wrong in human behaviour i. e. belief of what is morally correct or acceptable. It is so to say ethics is a moral philosophy which investigates normative questions about what people ought to do. Importance of ethics in our daily life is responsibility, loyalty integrity and respect. Socrates, the greatest Greek philosopher was the father of ethics. Immanuel Kant (1724 - 1804), the German philosopher is considered as the father of modern ethics and one of the greatest philosophers in the history of philosopher is regarded as the father of philosophy. Aristotle, the greatest Greek philosopher is regarded as the father of philosophy and morals.